2022
DOI: 10.1051/0004-6361/202244655
|View full text |Cite
|
Sign up to set email alerts
|

Toward measuring supermassive black hole masses with interferometric observations of the dust continuum

Abstract: This work focuses on active galactic nuclei (AGNs) and on the relation between the sizes of the hot dust continuum and the broad-line region (BLR). We find that the continuum size measured using optical/near-infrared interferometry (OI) is roughly twice that measured by reverberation mapping (RM). Both OI and RM continuum sizes show a tight relation with the Hβ BLR size, with only an intrinsic scatter of 0.25 dex. The masses of supermassive black holes (BHs) can hence simply be derived from a dust size in comb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 104 publications
0
2
0
Order By: Relevance
“…A final possible explanation for the excess emission is calibration issues between the RGS and PN instruments. There is a known correction needed between these instruments (see Appendix B of Grafton-Waters et al (2023), for details). However, we attempted to mitigate these effects by ignoring PN data below 0.5 keV, and we found that the excess emission was still present.…”
Section: The Featureless Continuummentioning
confidence: 99%
“…A final possible explanation for the excess emission is calibration issues between the RGS and PN instruments. There is a known correction needed between these instruments (see Appendix B of Grafton-Waters et al (2023), for details). However, we attempted to mitigate these effects by ignoring PN data below 0.5 keV, and we found that the excess emission was still present.…”
Section: The Featureless Continuummentioning
confidence: 99%
“…The error on the luminosity-based dust radius is determined by the error on the temperature and the error on the total accretion disk luminosity. Due to the relatively large wavelength coverage of the cross-dispersed near-IR spectra, which are also of relatively high signal-to-noise, the error on the temperature is small (∼10 − 30 K; Landt et al, 2019;2023). The accretion disk luminosity is mostly determined by the accretion rate, which is set by the flux level of the near-IR spectrum.…”
Section: Object Namementioning
confidence: 99%